1975
DOI: 10.3181/00379727-149-38853
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D3: Evidence of an Enterohepatic Circulation in Man

Abstract: AND VAY L. W. G O Mayo Clinic and Mayo Foundation, Rochester, Minnesota 5590125-Hydroxyvitamin D3 (25-OH-D3) is a metabolite of vitamin D3 that has greater biologic potency than D3 (1) and is the predominant form of vitamin D in plasma (2), where it circulates bound to specific carrier proteins (3). The physiologic role of 25-OH-D3 is not entirely understood, but it is a precursor of more polar and biologically active forms of vitamin D in deficient animals (4, 5). Physiologic quantities may not be directly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(40 citation statements)
references
References 7 publications
3
36
1
Order By: Relevance
“…Thus, D3 and VDR have a profound effect on the signal transduction mediated by bile acid/FXR. Since the reduction in the expression of BSEP and I-BABP may inhibit the enterohepatic circulation of bile acid, D3 may affect the intestinal absorption of D3 itself (Arnaud et al 1975) as well as lipophilic molecules, including T 3 /T 4 (DiStefano et al 1993), RA (Thompson & Strautnieks 2001), TZD (Kawai et al 2000), and 22(R)-HC. Our results also suggest that D3/VDR downregulates SHP expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, D3 and VDR have a profound effect on the signal transduction mediated by bile acid/FXR. Since the reduction in the expression of BSEP and I-BABP may inhibit the enterohepatic circulation of bile acid, D3 may affect the intestinal absorption of D3 itself (Arnaud et al 1975) as well as lipophilic molecules, including T 3 /T 4 (DiStefano et al 1993), RA (Thompson & Strautnieks 2001), TZD (Kawai et al 2000), and 22(R)-HC. Our results also suggest that D3/VDR downregulates SHP expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced efficiency of intestinal absorption of vitamin D, as a consequence of ileopathy (Haderslev et al, 2003), a disrupted enterohepatic circulation of vitamin D (Arnaud et al, 1975) and/or renal insufficiency (Freaney et al, 1993) have been suggested as possible contributory factors to the lower vitamin D status in CD patients. Disease activity (Harries et al, 1985;Tajika et al, 2004) has also been suggested to influence vitamin D status in CD.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis on entero-hepatic circulation of vitamin D was generated in the seventies based on observations in humans showing that considerable amounts of i.v. administered H 3 -labelled cholecalciferol or 25-OHD derivates appeared in the bile (20). Subsequent studies, however, revealed that vitamin D was mainly excreted as biologically inactive polar degradation products and that the amount of intact cholecalciferol or 25-OHD was negligible (21,22).…”
Section: Discussionmentioning
confidence: 99%